LACTOFERRIN AND FERRITIN IN A LABORATORY CONTROL OF A TOXICITY LEVEL OF ANTI-TUBERCULOSIS DRUGS - Igor Kuznetsov (Journal of Global Pharma Technology, 2016)
Introduction: The impact of anti-TB drugs has a huge load on the immune system, which often leads to the state of maladaptation. In this regard, it is necessary to develop new approaches to immunomodulation, which can be monitored in a laboratory by changes in concentration of ferroproteins of blood, lactoferrin and ferritin. In destructive forms of pulmonary tuberculosis, the level of lactoferrin and ferritin in blood decreases, and with the increase in their concentration, the condition of patients improves. Materials and Methods: The effect of immunomodulator trekrezan on the development of a toxicity level of anti-TB drugs was studied. The indicators of a toxicity level include: the increase in the total protein content, urea in blood serum, hemoglobin concentration, decrease in the number of red blood cells, increase in the number of leukocytes, lymphocytes, increasing activity of alanine aminotransferase and aspartate aminotransferase. We simultaneously examined the changes in the concentration of lactoferrin and ferritin. We studied 6 groups of patients with a diagnosis of Cavernous lung tuberculosis. Results: In the group which took only basic medication + trekrezan + pyridoxine (2 courses), the best positive changes were registered at the end of the course of chemotherapy. All the above-mentioned laboratory indicators were in the normal range. After one month of the treatment, lactoferrin increased by more than 10 times, and the concentration of ferritin increased significantly, with its subsequent normalization. Discussion: It is claimed that the higher the concentration of lactoferrin and ferritin, the stronger the body’s defenses, and the double course of trekrezan and pyridoxine extremely minimizes the toxicity of chemotherapy. Keywords: lactoferrin, ferritin, trekrezan, toxicity, immunity.